The Business and Administrative Correspondence Under the Kings of Ur - Sollberger, Edmond (1966)
1-5: Introduction; 6-92: The Letters; edition of 373 letters in Sumerian and Akkadian, Ur III period; 186 previously published; 93-192: Glossary; 831 entries; Plates; = 187 previously unpublished tablets; $18; below 29: Indices for listing of texts according to previous publications and museum classification.